2014
DOI: 10.1136/bjophthalmol-2013-304442
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different surgery procedures for convergence insufficiency-type intermittent exotropia in children

Abstract: The improved R&R procedure in which medial rectus resection based on the near deviation with lateral rectus recession based on the distant deviation has a better alignment than the UMR and BMR surgeries for the treatment of children with CI-type IXT. All the UMR, BMR and improved R&R surgery can reduce near-distance differences in children with CI-type IXT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…Wang et al found the success rate of unilateral R&R to be superior to either bilateral LR recession, bilateral MR resection, or unilateral MR resection in children with CI-XT. [14] In this study, the amount of MR resection was based on the near deviation and the LR recession based on the distance deviation. Utilizing this technique, a success rate of 85.7% was achieved, which was defined as the distance deviation in primary gaze to be between ≤10PD of exophoria/tropia and ≤5 PD of esotropia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al found the success rate of unilateral R&R to be superior to either bilateral LR recession, bilateral MR resection, or unilateral MR resection in children with CI-XT. [14] In this study, the amount of MR resection was based on the near deviation and the LR recession based on the distance deviation. Utilizing this technique, a success rate of 85.7% was achieved, which was defined as the distance deviation in primary gaze to be between ≤10PD of exophoria/tropia and ≤5 PD of esotropia.…”
Section: Discussionmentioning
confidence: 99%
“…In a direct comparison of reports of bilateral R&R with or without slanting, unilateral MR resection with or without slanting and unilateral R&R, it was found that unilateral R&R with MR resection based on the near deviation, and LR recession based on the distance deviation achieved the best alignment. [14] However, the success rates of the above procedures vary widely, ranging from 18% to 92%.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Surgical management is required for patients that do not respond to these measures or for patients whose deviations are too large or poorly controlled [3]. The various surgical procedures for CI-IXT include unilateral or bilateral medial rectus (MR) resection(s), bilateral lateral rectus (LR) recessions, unilateral LR recession combined with MR resection [4][5][6][7], MR resection with adjustable sutures [3], slanted bilateral MR resections [8][9][10], improved unilateral LR recession combined with MR resection [11][12][13], and slanted bilateral lateral rectus recession (SBLR-rec) [1-2, 14,15]. The reported success rates range from 13.3-92%.…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral medial rectus resection (BMRR) can be used in correcting CI‐type IXT (Hermann ; Choi & Rosenbaum ; Wang et al. ), because this approach can strengthen the medial rectus (MR), reduce near and distance deviations, and collapse the near‐distance differences.…”
Section: Introductionmentioning
confidence: 99%